👉 Try now NerdPal! Our new math app on iOS and Android

# Equations with Cubic Roots Calculator

## Get detailed solutions to your math problems with our Equations with Cubic Roots step-by-step calculator. Practice your math skills and learn step by step with our math solver. Check out all of our online calculators here.

Go!
Math mode
Text mode
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

###  Difficult Problems

1

Solved example of equations with cubic roots

$2\left(7b-1\right)^{\frac{1}{3}}=-4$
2

Removing the variable's exponent raising both sides of the equation to the power of $3$

$\left(2\sqrt{7b-1}\right)^{3}=-64$
3

The power of a product is equal to the product of it's factors raised to the same power

$8\left(7b-1\right)=-64$

4

Divide both sides of the equation by $8$

$\frac{8\left(7b-1\right)}{8}=-\frac{64}{8}$
5

Simplifying the quotients

$7b-1=-\frac{64}{8}$
6

Divide $-64$ by $8$

$7b-1=-8$
7

We need to isolate the dependent variable $b$, we can do that by simultaneously subtracting $-1$ from both sides of the equation

$7b=-8-1\cdot -1$
8

Multiply $-1$ times $-1$

$7b=-8+1$
9

Subtract the values $1$ and $-8$

$7b=-7$
10

Divide both sides of the equation by $7$

$\frac{7b}{7}=-\frac{7}{7}$
11

Simplifying the quotients

$b=-\frac{7}{7}$
12

Divide $-7$ by $7$

$b=-1$

$b=-1$